Love your Leave, Don't Leave your Love! Paid Parental Leave and Children's Living Arrangements - Kamila Cygan-Rehm; Daniel Kühnle; Regina T. Riphahn (Center for Economic Studies and ifo Institute (CESifo), 2017)
We examine how a German paid parental leave reform causally affected early childhood living arrangements. The reform replaced a means-tested benefit with a universal transfer paid out for a shorter period. Using a difference-in-differences design, we find that the reform increased the probability that a newborn lives with non-married cohabiting parents. This effect results from a reduced risk of single parenthood among women who gained from the reform. We reject the economic independence hypothesis and argue that the effects for reform winners are consistent with alternative hypotheses related to increased female financial attractiveness and increased paternal involvement in childcare.
Keywords: J12; J13; J18; I30; 330; parental leave; living arrangements; marriage; cohabitation; single motherhood; child well-being; early childhood